Modifications of the Fund's Conditionality Framework : Application to the Policy Support Instrument. (Policy Papers; Policy Paper ;, 2009)
In connection with its recent review of the GRA Lending Toolkit and Conditionality-Reform Proposals, the Executive Board decided that the Fund would move to a review-based approach to monitor the implementation of structural reforms in the context of Fund-supported programs, including under PRGF or ESF arrangements.